Transmission and shedding patterns of Salmonella in naturally infected captive wild roof rats (rattus rattus) from a Salmonella-contaminated layer farm - Umali, Dennis V.; Lapuz, Randy Rhon Simoun P.; Suzuki, Terumasa; Shirota, Kazutoshi; Katoh, Hiromitsu (University Knowledge Digital Repository, 2012)
Rodents play a major role in the transmission and maintenance of Salmonella contamination cycles in poultry facilities. However, very limited field data are available regarding the transmission routes, infection cycle, and shedding patterns of Salmonella by naturally infected wild rodents from commercial layer farms. In this study, a total of 128 resident wild roof rats (Rattus rattus) were captured from a Salmonella-contaminated layer facility. All roof rats were divided into 51 laboratory cages, and weekly monitoring of Salmonella fecal shedding patterns was conducted for 53 wk. Seven roof rats from cages that were observed to frequently shed Salmonella were isolated in individual cages, and daily Salmonella monitoring was performed for 35 days. At the end of monitoring, each roof rat was euthanatized, and isolation of Salmonella from different organs was performed. Results of weekly monitoring of Salmonella showed that 21 of 51 cages (41.2) were positive for Salmonella Infantis, while two cages (3.92) were positive for Salmonella Enteritidis. Moreover, 11 cages were positive for Salmonella for at least two sampling weeks. Isolation of Salmonella from fecal droppings was mainly observed during the first 12 wk of captivity. The longest interval between two Salmonella-positive fecal dropping was 24 wk. In the daily Salmonella monitoring, only Salmonella Infantis was isolated from fecal droppings, in which the highest number of Salmonella Infantis organisms per fecal dropping was at 1 × 108 colony-forming units (cfu), while the lowest measured quantity was 1 × 103 cfu. It was noted that the frequency of Salmonella shedding in fecal droppings appeared to have a linear correlation (r 0.85) with the number of Salmonella organisms (cfu) per fecal pellet (P < 0.05). Moreover, pulsed-field gel electrophoresis analysis of Salmonella Infantis isolates revealed a single identical pulsed-field pattern. Salmonella Enteritidis isolates from fecal droppings and internal organs also generated a single identical pulsed-field ...